Interactive Role of Psychological Capital and Social Capital on Organizational Commitment and Effective Training of Faculty Members - Abolfazl Ghasemzadeh-Alishahi; Zahra Heydarizadeh; Atiyeh Moosavi; Mohammad Hasani (Kerman University of Medical Sciences, 2015)
Background & Objective: Psychological capital is a new concept in the field of positive psychology and plays an important role in an individuals perceived and psychological health The current study was undertaken with the aim of determining the relationship among and predicting organizational commitment and effective training through psychological capital and with regard to the mediator role of social capital   Methods: In this descriptive correlational research and standard and researchermade questionnaires were used to collect data The study population consisted of all faculty members of Tabriz University of Medical Sciences Tabriz Iran (n = 650) Using the Morgan table 240 individuals were chosen through stratified random sampling For data analysis the Pearson correlation coefficient and deflator multiple regression were used in SPSS statistical software   Results: The research findings demonstrated a meaningful relationship between the variables The interactive role of psychological capital and social capital on organizational commitment and effective training among faculty members of Tabriz University of Medical Sciences was approved This means that among teachers with high social capital an increase in psychological capital was associated with an increase in commitment and effective training   Conclusion: These findings indicate the necessity of recognizing the interactive role of psychological capital and social capital on organizational commitment and effective training